Сarmen Echicum: Echo-Conversations in 17th-Century School Poetry - Kuznetsova, Olga (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
The aim of the article is to publish and discuss a little-known text from the end of the 17th century – a model representative of the poetic form called carmen echicum. Difficult fragments are commented upon and the plot is analyzed. A hypothesis about the piece’s place in its broader cultural context is put forward. A history of сarmen echicum in Russian literature is briefly outlined.